Health of secondary school students in terms of physical activity in their lifestyle - Bendíková, Elena; Novotná, Barbora; Marko, Michal (Diagnostics and Consultancy in Assisting Professions, 2018)
Health care is considered to be as a very wide range of various factors, which affect individual components of a health at all stages of a life, where a physical activity plays an important role. Therefore, an aim of a study was to identify a current state of selected lifestyle determinants in secondary school students with focus on the physical activity as a health-related aspect. A monitored group consisted of 80 adolescent students, of which 40 were female students (age 18.43 ± 1.3 years old, body weight 59.05 ± 5.6 kg and body height 166.65 ± 6.3 cm) and 40 were male students (age 18.55 ± 0.9 years old, body weight 76.2 ± 7.6 kg and body height 178.8 ± 6.9 cm) of Spišská Nová Ves who were the students of Secondary Vocational School of Economics. From the point of view of data acquisition methods, a survey was used, where results point to the following facts. Both genders, 60 % of male students and 52 % of female students feel healthy and in a good shape. From the point of view of a frequency of realization PA, in both genders is a dominant answer "3 times and more", which we evaluate positively, where an intensity of PA is dominant (male students 60 % and female students 60 %) of medium character. Up to 72 % of the female students reported a feeling of happiness after PA with a significant difference (χ2 = 6.003, p = 0.0136, p < 0.05) to a detriment of the male students. The lifestyle, from the point of view of the health, would like to change more female students (42.5 %) than male students (35 %). The study is a part of the research project VEGA 1/0242/17 „Physical activity as prevention of functional disorders related to the musculoskeletal system of secondary school students“.